KORELASI PANJANG TULANG FEMUR TERHADAP TINGGI BADAN DAN USIA PADA PRIA DEWASA SUKU BUGIS DI KOTA KARANG KECAMATAN TELUK BETUNG TIMUR KOTA BANDAR LAMPUNG - Anggraeni Janar Wulan; Hendro Sihaloho (Medula, 2021)
Estimates of height based on bone length is the femur bone are the most widely used methods, because they have good correlation coefficient values. This study was conducted using a descriptive analytical method with a cross sectional approach to 38 subjects who were over 21 years old and there were no bone abnormalities. The averages of height Bughis is 162,758 ± 6,09, length of femur bone Bughis right is 33,2 ± 3,09 and left is 32,158 ± 2,86. By using Pearson correlation analysis, the value of r = 0.855 for the right femur bone with height and r = 0.862 for the left femur bone with height very strongthWhich means a very strong relationship between the length of the femur bone with height. And the Bughis regression formula to estimate of height is Y = 106,767 + 1,683X (right) and Y = 102,026 + 1,835X (left), meanwhile Y = estimated height (cm) and X = Femur Bone Length. And for the correlation of femur length with age, r = -0.206 for the right femur bone and r = -0.223 for the left femur bone is weak. There is correlation of femur bone length to height and age in Bughis adult men at Karang City East Teluk Betung Subdistrict Bandar Lampung City.